Weed Management in the Soybean Crop - Silva, Alexandre Ferreira da; Galon, Leandro; Aspiazú, Ignacio; Ferreira, Evander Alves; Concenço, Germani; Júnior, Edison Ulisses Ramos; Rocha, Paulo Roberto Ribeiro (IntechOpen, 2013)
None